2006
DOI: 10.1111/j.1365-2516.2006.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the genotoxic effects of radiosynovectomy with Re‐186 in paediatric age group undergoing therapy for haemophilic synovitis

Abstract: The major finding of this study with relatively small sample is that, radiosynovectomy with Re-186 does not seem to induce early genotoxic effects on the peripheral blood lymphocytes in paediatric age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
0
20
0
6
Order By: Relevance
“…Turkmen et al. [17] reported a safety study in 20 boys with haemophilia who had undergone RS with Re 186 . In this study, cytogenetic analyses were evaluated and there were no significant differences between baseline and the day 90 control.…”
Section: Discussıonmentioning
confidence: 99%
“…Turkmen et al. [17] reported a safety study in 20 boys with haemophilia who had undergone RS with Re 186 . In this study, cytogenetic analyses were evaluated and there were no significant differences between baseline and the day 90 control.…”
Section: Discussıonmentioning
confidence: 99%
“…However, as outlined above some patients who still had CBs even after 1 year of observation and de novo chromosomal changes after radioisotopic exposure may be accepted as warning signals for young population. Turkmen et al [17] reported a safety study in 20 boys with hemophilia who had undergone RS with 186 Re. They used micronucleus assay as in our study to evaluate DNA damage in these patients.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the chromosomal changes after RS, several authors have shown that genotoxic radiation doses delivered to the peripheral lymphocytes are not statistically significant (17,18,19,20,21). However, transient increase in micronuclei of peripheral lymphocytes may be expected soon after Y-90 therapy which disappeared at 90 th .…”
Section: Introductionmentioning
confidence: 99%
“…However, transient increase in micronuclei of peripheral lymphocytes may be expected soon after Y-90 therapy which disappeared at 90 th . day (20). …”
Section: Introductionmentioning
confidence: 99%